Arthrodesis of the proximal interphalangeal joints of a hindlimb in a heifer - Muggli, E.; Weidmann, E.; Bruderer, A.; Nuss, K. (Veterinary and Comparative Orthopaedics and Traumatology, 2015)
A two-year-old Braunvieh heifer was presented with a traumatic luxation of the second phalanx of the medial digit and concurrent subluxation of the second phalanx of the lateral digit of the right hindlimb. Closed reduction of both luxations was possible. Surgical arthrodesis was achieved using one narrow 4.5 mm three-hole equine locking compression plate for each joint. Placement of the bone plates resulted in stable arthrodesis of both proximal interphalangeal joints of the right hindlimb but there was persistent residual lameness. The heifer delivered a healthy calf but was slaughtered eight months after surgery because of varus deformity of the contralateral limb. Radio-graphs taken post-mortem revealed pronounced periosteal reactions involving both proximal interphalangeal joints and only partial bony bridging of the joint spaces.
Keywords: Cattle; proximal interphalangeal joint; luxation; arthrodesis; locking compression plate